Experimental Demonstration of Dark‐State Metasurface Laser with Controllable Radiative Coupling. Issue 12 (8th April 2022) - Droulias, Sotiris; Mohamed, Sughra; Rekola, Heikki; Hakala, Tommi K.; Soukoulis, Costas M.; Koschny, Thomas
Abstract: Lasing at the nanoscale using plasmonic nanoparticles offers the prospect of strong field concentration, hence strong light−matter interactions, low lasing thresholds, and ultrafast operation. However plasmonic nanoparticles suffer from high dissipative and radiative losses, the latter being rigidly tied to the shape of the nanoparticles and symmetry of their localized plasmon resonant modes. To overcome this limitation, recent theoretical work proposes using direct lasing into dark surface states to construct lasers that conceptually allow for independent implementation of the lasing state and its coherent radiation output. Here, lasing in dark resonant states of a metasurface laser and controllable coherent outcoupling of radiation with the aid of a tightly coupled, weakly radiative metasurface are demonstrated experimentally. The laser is implemented using a thin, low‐loss dielectric film supporting surface mode‐like dark dielectric bound states and the coupling metasurface is composed of small non‐resonant scatterers that controllably but weakly perturb the dark mode and turn it partially bright. Distinct far‐field signatures that can be observed experimentally for both dark and bright lasing are identified and demonstrated. The scalability of this design, here implemented for lasing in the near‐infrared, enables large‐aperture ultra‐thin coherent light sources with controllable emission from the infrared to the visible. Abstract : An experimental demonstration of lasing in dark resonant states of a metasurface laser and controllable coherent outcoupling of radiation with the aid of a tightly coupled, weakly radiative metasurface is presented. It is shown that using direct lasing into dark surface states conceptually enables independent implementation of the lasing state and its coherent radiation output.